HPLC-DAD-MS/MS-ESI screening of phenolic compounds in Pieris brassicae L. reared on Brassica rapa var. rapa L.. - Ferreres, F. (2008)
The phenolic profiles of cabbage white butterfly (Pieris brassicae L.; Lepidoptera: Pieridae) at different development stages (larvae, exuviae, and butterfly), its excrements, and its host plant Brassica rapa var. rapa L. were determined by high performance liquid chromatography- diode-array detector-mass spectrometry/mass spectrometry-electrospray ionization (HPLC-DAD-MS/MS-ESI). Twenty-five acylated and nonacylated flavonoid glycosides and ferulic and sinapic acids were identified in host plant, from which only 12 compounds were found in the excrements. In addition, the excrements showed the presence of sulfate flavonoids and other flavonoid glycosides that were not detected in the leaves. In the larvae kept without food for 12 h, only 3 compounds common to the plant material and 2 others, also present in the excrements, were characterized. The results indicate that deacylation, deglycosylation, and sulfating steps are involved in the metabolic process of P. brassicae and that its excrements may constitute a promising source of bioactive compounds, which could be used to take profit of this common pest of Brassica cultures.